2001
DOI: 10.1088/0964-1726/10/5/316
|View full text |Cite
|
Sign up to set email alerts
|

Vibration-based damage assessment utilizing state space geometry changes: local attractor variance ratio

Abstract: A novel feature extracted from a nonlinear time series is presented within the context of vibration-based damage detection in a system. An eight-degree-of-freedom spring-mass-damper 'structure' is considered with damage incurred by a stiffness degradation in one spring. The system is excited with a chaotic input, and by tuning the Lyapunov exponents of the chaotic excitation to the dominant eigenvalue of the structure the dimensionality of the entire system is effectively controlled. Both the input and output … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(118 citation statements)
references
References 22 publications
4
114
0
Order By: Relevance
“…It can be concluded that: 1) The influence of the temperature changes is essential and can change substantially the nonlinear dynamic response of the plate and this is why temperature changes should be taken into account when developing a damage assessment procedure; 2) Temperature loadings which lead to either buckling or chaotic behaviour of the plate, might render the damage criterion suggested by Eqs. (18), (19) and (20) inappropriate. This is because even small damage, resulting in stiffness reduction of the plate, could lead to dramatic changes in the Poincaré maps of the response and consequently to unreliable results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It can be concluded that: 1) The influence of the temperature changes is essential and can change substantially the nonlinear dynamic response of the plate and this is why temperature changes should be taken into account when developing a damage assessment procedure; 2) Temperature loadings which lead to either buckling or chaotic behaviour of the plate, might render the damage criterion suggested by Eqs. (18), (19) and (20) inappropriate. This is because even small damage, resulting in stiffness reduction of the plate, could lead to dramatic changes in the Poincaré maps of the response and consequently to unreliable results.…”
Section: Discussionmentioning
confidence: 99%
“…The pseudo-load mode superposition method (PLMS) [2,11,[18][19][20][21] is applied to solve the problem for nonlinear vibration of plates. It will be only briefly presented here.…”
Section: Numerical Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Any changes to the system resulting from damage alter the way in which the signal is filtered. The benefits of using a chaotic excitation of the system relate to the way attractor stability (in the Lyapunov sense) and geometry (dimension) interact, and this is discussed in detail in [84].…”
Section: Chaotic Interrogation Of a Damaged Beammentioning
confidence: 99%